Mechanized cultivation in safflower (Carthamus tinctorius L.): Mechanized cultivation in safflower (Carthamus tinctorius L.) - S V KHADATARE; L N TAGAD; D R MURUMKAR; S I TAMBE (Journal of Oilseeds Research, 2023)
The objective was to introduce mechanization in safflower based cropping systems and compare it with traditional method without mechanization and work out energy budgeting and economics. The un-replicated field experiment was conducted in the year 2018-19, 2019-20 and 2020-21 with two sets of treatments (mechanization and farmer’s practice) on an area of 25x70 sq.m. The safflower variety SSF 708 was sown in 45x20 cm spacing. Mechanized cultivation in safflower recorded significantly higher yield of safflower than farmer practice. The seed yield increase was 13.9% under mechanized condition than farmer’s practice. About Rs 5000/ha and time was saved in mechanized condition.